Association of perceptions of artificial light-at-night, light-emitting device usage and environmental noise - Espey, Brian (My University, 2022)
Exposure to artificial light-at-night (ALAN) is increasing globally, and there are concerns around how ALAN may impact sleep, psychological and physical health. However, there is a lack of evidence in the literature on how individuals perceive ALAN relative to their sleeping environment and habits, and how such perceptions correspond to objectively assessed night-time illuminance at the level of the residence. This cross-sectional study examined how such perceptions associate with sleep quality, sleep timing, psychological distress and cognitive failures. Further we examined the association between illuminance levels calculated as the biologically-relevant melatonin-suppression index (MSI) and the self-report of perception of ALAN. Five hundred and fifty two adult participants completed a survey addressing perception of ALAN in sleep environment along with the Pittsburgh Sleep Quality Index, Munich Chronotype Questionnaire, Cognitive Failure Questionnaire and the General Health Questionnaire. We report that perception of external ALAN in the sleeping environment was associated with poorer sleep quality, more cognitive failures and greater psychological distress, when controlling for age, sex, house location and MSI. No associations were found between the perception of external ALAN and MSI scores, and MSI scores were not associated with scores on any of the self-report measures. Internal lighting passing into the sleeping environment was associated with poorer sleep quality but not with psychological wellbeing. Habitual use of light-emitting devices was associated with poorer psychological wellbeing but not with sleep quality and sleep timing. Perception of environmental noise annoyance at night was associated with higher psychological distress and poorer quality sleep, and the perception of noise annoyance was associated with perception of ALAN. These results may suggest heightened attentional bias towards ALAN associated with poor sleep quality and higher levels of psychological distress, and highlight the need for more granular approaches in the study of ALAN and sleep and psychological health in terms of levels individual ALAN exposure, and an interpretation that seeks to integrate biological and psychological perspectives.
PUBLISHED
Keywords: Light pollution; Sleep; Mood; Circadian; Cancer; Light Pollution; Chronic Health Condition; Emotional-behavioural Problems; Environment and housing